Intention to Get COVID-19 Vaccinations among Ophthalmology Residents in Poland: A Cross-Sectional Survey - Joanna Konopińska; Iwona Obuchowska; Łukasz Lisowski; Natalia Dub; Milena Kozera; Marek Rękas (Vaccines, 2021)
This study aimed to evaluate the acceptability of coronavirus disease of 2019 (COVID-19) vaccination among ophthalmology residents in Poland. An online, self-administered, anonymous survey was distributed among Polish ophthalmology residents in early 2021. Of 126 residents who completed the survey, 71.4% indicated that they would get vaccinated, 17.5% were unsure, and 11.1% would refuse vaccination. Married respondents with children (p = 0.036) and respondents living with their families (p = 0.310) were more likely to accept vaccination, believing that the vaccine is effective (p = 0.002 and p = 0.001, respectively), and fearing for themselves (p = 0.031 and p = 0.023, respectively) or their families (p = 0.032 and 0.055, respectively) getting infected. Respondents who contracted COVID-19 often reported the expected relief in sanitization (p = 0.011) as their reason for vaccination, and the previous severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection (p = 0.050) as their reason for not vaccinating. Unmarried residents and residents living alone often declared that they were waiting for the effectiveness and long-term complications of the vaccine to be assessed (p = 0.005, both). Residents living with their families were significantly less likely to report COVID-19 as the reason for refusing vaccination (p = 0.022). In conclusion, most ophthalmology residents expressed a willingness to get vaccinated. Marital status and cohabitants affect vaccination acceptance. People with COVID-19 have different reasons for accepting or refusing vaccination. Medical authorities should persuade citizens more to vaccinate.